Education, Training, and Practices of Neurorehabilitation in India During the COVID-19 Pandemic - Surya, Nirmal; Srivastava, Abhishek; Nagda, Taral; Palande, Deepak; Someshwar, Hitav (Frontiers in Neurology, 2021)
Background: Corona virus disease (COVID-19) was declared a pandemic by the World Health Organization in March 2020. This has affected service delivery among all medical disciplines in India including neurorehabilitation services. Aims and Objectives: The aims and objectives of the study were to assess the effect of COVID-19 pandemic on neurorehabilitation services across India. Methodology: A prospective nationwide survey study was undertaken by the Indian Federation of Neurorehabilitation during the pandemic. A questionnaire was prepared using Google forms software consisting of four sections: demography, neurorehabilitation practice before COVID-19 pandemic, neurorehabilitation practice during COVID-19 pandemic, and continuing medical education during COVID-19 pandemic. Results: Responses (872) were received from neurorehabilitation professionals across the country out of which 2.2% professionals did not give consent for participating in the survey. Participants (36.6%) were practicing traditional or independent referral basis rehabilitation, while 63.4% participants were practicing multidisciplinary rehabilitation. On an average, respective units were conducting 500–750 therapy sessions per month. Majority of the rehabilitation units in India lacked a physiatrist, rehabilitation nurse, music therapist, cognitive therapist, and urologist. Approximately 80% of the rehabilitation units have the basic rehabilitation modalities and advance technology was present in only 20% of the rehabilitation units. During COVID-19 pandemic, 19.5% centers were providing elective services, 50.3% emergency services, 15.6% new outpatient services, and 22.7% were providing follow-up outpatient services. Centers (51.5%) were providing telerehabilitation services for neurological conditions during the times of COVID-19 pandemic. Professionals (61.1%) providing telerehabilitation were working from home. Among the patients who needed neurorehabilitation, 28% were doing their exercises independently, 31% were supervised by caregivers, 17% were supervised by therapists, and 24% were not receiving any therapy. Participants (95.5%) wanted to receive more training in the field of neurorehabilitation. The participants utilized webinars (71%), online courses (22%), case discussion forums (19%), panel discussions (13%), and literature search (8%) during COVID-19 pandemic to continue education. Conclusion: The study reflects the situation of neurorehabilitation service delivery in India during the pandemic as the respondents were from all parts of the country and included most components of the neurorehabilitation team. Neurorehabilitation services were severely affected across India during the COVID-19 pandemic. Tele-neurorehabilitation has emerged as a new service delivery model during the pandemic. Online means of education has emerged as the primary source of continuing medical education during the pandemic.